2022
DOI: 10.1186/s12933-022-01577-7
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index trajectory and stroke incidence in patients with hypertension: a prospective cohort study

Abstract: Background It has been suggested that the baseline triglyceride-glucose (TyG) index, a simple surrogate measure for insulin resistance, is significantly associated with the occurrence of stroke. Nevertheless, the impact of longitudinal patterns of TyG on the stroke risk in hypertensive patients is still unknown. Hence, this study aimed to investigate the association between TyG index trajectory and stroke risk among hypertensive patients. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…It was recently noted that the variability and longitudinal trajectory in the TyG-index, both regarded as novel and important indicators for outcome events, had strong predictive effects for cardiovascular diseases [35][36][37][38]. With either variability or longitudinal trajectory in the TyG-index, the effects on CMDs risk in this research are consistent with a previous study that found those indicators (variability and trajectory) to be associated with CMDs risk.…”
Section: Discussionsupporting
confidence: 87%
“…It was recently noted that the variability and longitudinal trajectory in the TyG-index, both regarded as novel and important indicators for outcome events, had strong predictive effects for cardiovascular diseases [35][36][37][38]. With either variability or longitudinal trajectory in the TyG-index, the effects on CMDs risk in this research are consistent with a previous study that found those indicators (variability and trajectory) to be associated with CMDs risk.…”
Section: Discussionsupporting
confidence: 87%
“…A prospective study of 54,098 participants demonstrated that patients with higher TyG index experienced a 1.30-fold increased risk of IS [ 19 ]. Huang et al reported that long-term elevated TyG index in hypertensive patients was significantly associated with an increased risk of stroke, especially IS [ 20 ]. However, Zhao et al demonstrated a high TyG index was not associated with nondiabetic patients with non-ST-elevation myocardial infarctions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently noted that the variability and longitudinal trajectory in the TyG-index, both regarded as novel and important indicators for outcome events, had strong predictive effects for cardiovascular diseases ( 39 42 ). With either variability or longitudinal trajectory in the TyG-index, the effects on CMDs risk in this research are consistent with a previous study that found those indicators (variability and trajectory) to be associated with CMDs risk.…”
Section: Discussionmentioning
confidence: 99%